Suppression of a single pair of mushroom body output neurons in Drosophila triggers aversive associations. Issue 4 (22nd February 2017) - Ueoka, Yutaro; Hiroi, Makoto; Abe, Takashi; Tabata, Tetsuya
Abstract : Animals have evolved neural mechanisms that filter useful information from the complex environment in order to form memories. In Drosophila melanogaster, we found that a single pair of GABAergic neurons (MBON‐γ1pedc) could inhibit the effects of dopaminergic neurons, resulting in the suppression of aversive memory acquisition. In this way, the important information is highlighted and memorized. Abstract : Memory includes the processes of acquisition, consolidation and retrieval. In the study of aversive olfactory memory in Drosophila melanogaster, flies are first exposed to an odor (conditioned stimulus, CS+) that is associated with an electric shock (unconditioned stimulus, US), then to another odor (CS−) without the US, before allowing the flies to choose to avoid one of the two odors. The center for memory formation is the mushroom body which consists of Kenyon cells (KCs), dopaminergic neurons (DANs) and mushroom body output neurons (MBONs). However, the roles of individual neurons are not fully understood. We focused on the role of a single pair of GABAergic neurons (MBON‐γ1pedc) and found that it could inhibit the effects of DANs, resulting in the suppression of aversive memory acquisition during the CS− odor presentation, but not during the CS+ odor presentation. We propose that MBON‐γ1pedc suppresses the DAN‐dependent effect that can convey the aversive US during the CS− odor presentation, and thereby prevents an insignificant stimulus from becoming an aversive US.